From the peripheries of Santiago de Cali: a methodological approach to the creation of sociocultural and media representations by subordinate social groups in digital media - Noscué Mera, Eliana (2019)
This article describes the experiences related to the creation of sociocultural and media representations in digital social media (Facebook, Instagram, YouTube) during the development of the digital literacy pedagogical process called Alto Nápoles en Red. Said process is part of the methodological techniques used in a doctoral thesis in communication at present in construction. These qualitative techniques were developed with an involuntary-migrant community displaced by force from rural areas of southwestern Colombia (department of Cauca) and settled in one of the peripheries of Santiago de Cali. The paper aims to give an account of the possibilities, resistances and historical obstacles that these subordinate social groups have experienced in the framework of the internal armed conflict in Colombia. That is, its objective is to know about the uses and appropriations of digital ICT based on cultural differences, socioeconomic inequalities and media disconnections.